'Don't You Dare to Vote With the Communists!': Timeliness, Nostalgia, and the Authenticity of Experience in I'm a Communist Biddy!. (3rd July 2014) - Komporaly, Jozefina
Abstract : This article investigates the parallel adaptation processes between genres and media of Dan Lungu's celebrated Romanian novel I'm a Communist Biddy! (2007). Drawing on Stere Gulea's film adaptation ( Sunt a babă comunistă !, MediaPro Pictures, Romania, 2013) and Tamara Török and Judit Csoma's stage version ( Egy komcsi nyanya vagyok!, Katona József Theatre, Budapest, 2013), the article observes that neither film nor play are governed by an agenda of fidelity to the source text, and they depart from the literary source because of a new historical and economic context, in which the preoccupation with the communist era remains a timely endeavour all the same. Both versions strive for authenticity in terms of location and time period, and to this end they opt for an elaborate recreation of the past in the film and a reduction to literal levels of austerity onstage. Thus, both cinematic and stage adaptation operate as explorations into the protagonist's past, and in this sense they are illuminating works of art about personal memory, embedded to a certain extent, within collective memory. The adaptations strive to accurately represent selected notions of history, in parallel with which they also create alternative temporalities that mythologize history and favour a nonlinear sense of time. For this reason, I read these adaptations—ranging from transposition to commentary—as a form of translation, that explores the relationship between women and history and intertwines a cluster of influences, from historical plays and films, memory and verbatim plays, as well as staged biographies and enactments 'on location'.